1995
DOI: 10.1097/00000658-199506000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Results of Pancreas Transplantation with Portal Venous and Enteric Drainage

Abstract: These results indicate that PE and SB pancreas transplantation are equivalent in terms of patient and graft survival and suggest that the PE approach is associated with a decreased incidence of metabolic and bladder-related complications. In addition, the PE approach eliminates the state of peripheral hyperinsulinemia that characterizes the SB procedure. Continued follow-up will be necessary to determine if long-term outcomes will differ for patients with PE and SB grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
1
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 24 publications
5
80
1
6
Order By: Relevance
“…The results of the present study clearly show that hyperinsulinemia is associated with KPT-S and confirm our previous findings (2) as well as those of others (5,27). The demonstration of higher insulin response to glucose despite a similar C-peptide response, similar immunosuppressive regimen, and similar renal function in KPT-S recipients versus KPT-P recipients supports the concept that the hyperinsulinemia in KPT-S is due to diminished insulin clearance (3) and not simply from compensatory hypersecretion of insulin due to the immunosuppressive drugs and denervation of the pancreas graft (6).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of the present study clearly show that hyperinsulinemia is associated with KPT-S and confirm our previous findings (2) as well as those of others (5,27). The demonstration of higher insulin response to glucose despite a similar C-peptide response, similar immunosuppressive regimen, and similar renal function in KPT-S recipients versus KPT-P recipients supports the concept that the hyperinsulinemia in KPT-S is due to diminished insulin clearance (3) and not simply from compensatory hypersecretion of insulin due to the immunosuppressive drugs and denervation of the pancreas graft (6).…”
Section: Discussionsupporting
confidence: 94%
“…Others (5,(25)(26)(27), as well as our group (2), have shown that this new technique results in fewer postoperative complications and less peripheral hyperinsulinemia compared with the systemic-bladder approach. Because hyperinsulinemia is associated with insulin resistance and perhaps with an increased risk of cardiovascular disease (28,29), and because portal anastomosis of the pancreas graft reestablishes a more physiological state of insulin delivery and normalizes peripheral insulin levels, it has been argued that it may lead to normalization of the metabolic profile of the patients and to a reduction of cardiovascular complications (27). However, the effects of KPT-S versus KPT-P on peripheral and hepatic insulin action as well as on VLDL metabolism have not been previously investigated.…”
mentioning
confidence: 85%
“…Currently, we rarely use open pancreatic biopsy or percu taneouspancreaticbiopsy. Our data and those of Gaber et al [ 11] suggestthat the portalâ€"en teric technique is not associated with signifi cant delay in diagnosis or treatment of rejection and offers significant advantages. For thesereasons, this techniqueis now being eval uated at a number of major transplantcenters, and we believe that this technique will be more widely applied and that radiologists should be come familiar with the radiologic appearance of uncomplicated and complicated pancreatic allograft transplants.…”
Section: Discussionsupporting
confidence: 69%
“…RESEARCH DESIGN AND METHODS -Type 1 diabetic patients (n ϭ 11) after successful combined PKT were matched for age, sex, and BMI with nine healthy control subjects and six nondiabetic patients after successful kidney transplantation (Table 1). Type 1 diabetic patients (duration of type 1 diabetes: 31 Ϯ 2 years) had received a whole pancreas with systemic venous anastomosis to the iliac vein (2.4 Ϯ 0.5 years [range 0.8 -5.2]) before the study (12). By this method of systemic drainage, pancreatic endocrine secretions bypass the physiological first-pass clearance of the liver (9,12,20).…”
mentioning
confidence: 99%